A survey on online learning session of the blended learning mode among lecturers / Zubainun Mohamed Zabidi ... [et al.] - Mohamed Zabidi, Zubainun; Zakaria, Nurul Aimi; Ramli, Fariesha Farha; Alias, Ahmad Nazib; Mohd, Thuraiya; Baharun, Norhayati (UiTM Press, 2020)
Graduates who are deemed to be knowledgeable, marketable, equipped with problem solving and critical thinking skills are what most universities aspire to produce. This kind of graduates are considered an asset to any organisation and are in constant demand because they are equipped with hard skills as well as soft skills. Thus, lecturers are constantly striving to find effective teaching strategies that encourage meaningful learning among their learners. In order to make the process of learning more efficient, interesting and engaging for the learners a majority of lecturers are constantly aiming to innovate and thus improve their teaching techniques. One of their teaching strategies is online learning. This study investigates the culture of online learning session of the blended learning mode among the lecturers in Diploma Science programme. Quantitative research approach was used for data collection and analysis in the study. Findings from the study shows the lecturers use various medium to conduct online learning where the most popular is i-Learn while the least is Facebook. The most common activities during online session was uploading the e-content. 70% of lecturers spend between six to 10 hours of their working time to fulfils the one-hour online session for every week and most of the lecturers spends two weeks to finish the evaluation of student’s work.